APPLICATION OF INCLUSIVE DESIGN PRINCIPLES TO TESTING EFL DYSLEXIC STUDENTS - Łodej, Monika (Neofilolog, 2020)
There are two main challenges with inclusive testing of EFL students with dyslexia. First, application of inclusion may, paradoxically, involve exclusion of SEN students. Second, there is evidence for inconsistent policies relating to internal and external testing practices. The present paper reports on the application of inclusive design principles to the language testing of EFL students with dyslexia. Specific cognitive demands characteristic of dyslexia are mapped against both the types of accommodations made for SEN students and the principles of inclusive design. The results show a high degree of applicability of inclusive design principles in testing EFL students with dyslexia. Specifically, the data point to a strong alignment between presentation and response accommodations and five areas of weaknesses in dyslexia. The review concludes with a discussion on the benefits and limitations of inclusive testing in dyslexia. It is hoped that this study will advise testing boards, EFL teachers, as well as education and assessment services on the application of inclusive practices to testing EFL dyslexic learners.